PSYCHOLOGICAL SUPPORT GROUPS FOR HOSPITAL PATIENTS UNDERGOING TREATMENT IN THE RADIOTHERAPY DEPARTMENT - Muric, Damira; Raspopovic, Milena (HEALTH CARE, 2021)
Introduction/Aim: Research has shown that psychosocial support activates patients’ resources and provides a better quality of life to oncology patients who struggle with the disease and side-effects of the therapy. The aim of this study was to examine whether connecting hospitalized patients based on a similar emotional experience during treatment could help them in coping and accepting the treatment. Methods: In September 2019, we began the program of psychological support groups with patients at the Department of Radiotherapy of the Institute of Oncology, Clinical Center of Montenegro. While designing the content of the workshops, we used our own knowledge in the field of health psychology, applied psychological techniques and psychotherapy, and placed special emphasis on mindfulness or full awareness. Our sample consisted of 58 workshop participants, 36 were women and 22 were men. The workshops consisted of 7 segments and they were organized once in a month during six months and lasted 1 hour and 30 minutes. The workshops were organized as focus groups, while the moderator was a psychologist. All statements were recorded with a dictation machine and later analyzed. Results: Qualitative analysis of the content of the workshops and subsequent monitoring of patients who went through them shows that organizing support groups has its meaning and purpose and many benefits, primarily in the field of accepting the illness, overcoming emotional blockages, strengthening self-capacity and focusing on other life circumstances, besides their disease. Conclusion: It is necessary to organize this type of workshops for patients who are treated on an outpatient basis, as well as to introduce new segments in the content of the workshops.